PEMANFAATAN APLIKASI TIKTOK SEBAGAI MEDIA PEMBELAJARAN BAHASA DAN BUDAYA LAMPUNG - Husin, Sudirman (Jurnal Tiyuh Lampung: Pendidikan Bahasa dan Kebudayaan, 2023)
The purpose of this research is to determine the influence and benefits of the TikTok application on students' learning of Lampung language and culture. This is important to study because currently students' Lampung language and cultural skills are very low and there is minimal attention from schools, so this could cause the preservation of Lampung language and culture to be threatened. The method used in this research is a descriptive method using a qualitative approach. This research uses literature study as a data collection method needed to strengthen the hypothesis contained in the writing of this scientific work. Based on the results and discussion of this development research, it can be concluded that the conditions for learning Lampung language and culture in schools do not involve students and tend to be boring, so it is necessary to create learning conditions that are able to attract students' interest. Motivate students to learn and enjoy Lampung language and culture. Therefore, social media such as the TikTok application, which is currently popular among young people, can be used as learning material for students so that students are even encouraged to learn Lampung language and culture independently.